Validating the Application of the TPACK Model Associated with the Skills of Phonological Awareness and Letter Knowledge of Preschool Educators - Fernández-Chávez, Carolina (2022)
Objective. This study aimed to validate an instrument that allows knowing the perception nursery educators have about their disciplinary, pedagogical, and technological knowledge when they incorporate ICT in teaching two skills that underlie learning to read and write: phonological awareness and letter knowledge. Methodology. This research was a non-experimental, cross-sectional, quantitative study. A Likert-type survey, composed of 54 items that collect information from seven dimensions considered by the TPACK model, was used as an instrument. Thirty nursery educators participated in this study; they work with children of Transition level (early childhood education) from municipal schools in Penco, province of Concepción, Chile. For the validation of the instrument, the expert judgment technique was used, according to the method of Lawshe (1975) and the modifications made by Tristán-López (2008); for its reliability, the internal consistency coefficient Cronbach’s alpha was considered. Results. The main results indicate that the scale has high reliability and significant positive correlations, which indicates that it is a valid tool to be used as a diagnostic instrument that will identify the weaknesses and strengths of nursery educators in terms of their knowledge regarding the use of ICT for educational purposes in written language.